Quality Planting Material Production of Elephant Foot Yam through Farmers Participatory Approach in the Tribal Belts of Kerala - Sunitha, S; George, James; Muthuraj, R; Sheela, M N; Makeshkumar, T (JOURNAL OF ROOT CROPS, 2017)
Multiplication and distribution of quality planting materials of tuber crops is one of the major limitations for the undue delay in the spread of high yielding varieties among the farmers. An attempt was made to involve tribal farmers of Attappadi region of Palakkad and Wyanad districts of Kerala for quality planting material production of elephant foot yam, one of the tropical tuber crops attaining commercial status nowadays. The programme was implemented under the project on Development of tuber crops financed by Govt. of Kerala during 2013-14 and 2014-15. Fifty tribal famers were selected from Agali panchayat of Attappadi, Palakkad and Amblalavayal panchayat of Wyanad. Quality planting materials of variety Gajendra, were distributed to 50 beneficiary farmers for covering an area of 10 cents each, thus covering a total of 2 ha in each location. Multiplication was carried out under the direct supervision of ICAR-CTCRI scientists under rainfed conditions. Farmers got an average yield of 3-5 kg per plant by planting 500g seed corms. Based on random sampling, an average corm yield of 42.5 and 60.12 tha -1 was estimated at Agali and Ambalavayal respectively. Keeping aside 20% of the produce for own planting and home consumption, rest was available for disposal among the neighboring farmers and nearby areas for planting. The area expansion possibility was estimated based on the seed supply chain over a period of three years. It was projected to cover an area of 1000 ha with the improved variety Gajendra, within a period of three years, if the seed chain goes successfully.